Akibat yang ditimbulkan dari pembatalan perkawinan - Mahanani, Maulida Putri (Maliki Interdisciplinary Journal, 2024)
Marriage annulment is caused by the presence of several conditions that are not fulfilled. These conditions have been explained in fiqh and become the basis for the continuation of the marriage intended to avoid a marriage that is void. The cancellation of a marriage is the same as a divorce, so efforts are needed to avoid this before it happens. The consequences of an annulled marriage are serious, so it is necessary to prevent the marriage from being annulled.